Usahatani Padi Inpari 42 di Lahan Tadah Hujan Kabupaten Ogan Komering Ilir Sumatera Selatan - Waluyo Waluyo; Suparwoto Suparwoto; Atekan Atekan (Seminar Nasional Lahan Suboptimal, 2020)
Waluyo W, Suparwoto S, Atekan A.  2020. Rice farming of inpari 42  in rainfed land, ogan komering ilir district, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Superior varieties are one of the technological components that have a real role in increasing the production and quality of agricultural commodities, including superior varieties that are adaptive and have high yield potential in rainfed land. The purpose of this study was to determine the productivity and feasibility of farming Inpari 42 rice in rainfed rice fields. The research was conducted in Lubuk Seberuk Village, Lempuing Jaya Sub District, Ogan Komering Ilir District , South Sumatra, starting from December 2019 to May 2020. Locations and farmers were chosen intentionally. The demonstration plot was carried out on a 2 hectare farmer's land with tandur jajar legowo technology and balanced fertilization involving 2 farmers. Data collection method is by keeping farm record. The parameters observed were productivity, labor force and farm costs. The financial analysis of rainy season rice farming  provides a value of profit over cash or a total cost of IDR 22,025,000 with  B/C ratio of 2.51. So the superior variety of Inpari 42 rice grown in rainfed rice can be developed on a wider scale.